Understanding Trust in News: The Role of News Literacy in New Zealand - Cheung, Olivia (Auckland University of Technology, 2025)
This research investigates the relationship between news literacy and trust in news and journalism in New Zealand. Using a mixed-methods approach, including a nationwide survey and semi-structured interviews, the study applies the 5Cs framework of news literacy, focusing specifically on the domains of context (understanding external influences on journalism) and creation (understanding how journalism is produced). The findings show that while New Zealanders are highly aware of the economic, political, and technological pressures affecting the news industry, but their understanding of journalistic processes such as editorial decision-making and ethics is limited. This disconnect contributes to four major public concerns: political influence, attention-driven journalism, inconsistent quality of news in the digital environment, and lack of transparency in newsroom operations. The study identifies three types of news consumers: (1) Context + Creation Aware, who are critically informed and selectively trusting; (2) Context-Dominant, who recognise external pressures but have limited insight into how journalism works; and (3) Surface Awareness, who tend to trust based on familiarity or emotional resonance rather than deeper knowledge. The research concludes that improving news literacy, especially in terms of understanding context and creation, is essential for rebuilding public trust and supporting journalism’s democratic role.